Peran Bawaslu Dalam Mengawasi Netralitas Aparatur Sipil Negara Pada Pilkada 2024 di Kabupaten Pinrang - Irwan, Irwansyah; Sapri, Sapri; Sellang, Kamaruddin; Mannu, Ahmad (Saraq Opat: Jurnal Administrasi Publik, 2025)
The Role of Bawaslu in Supervising the Neutrality of State Civil Apparatus in the 2024 Pilkada in Pinrang Regency. Supervised by Sapri and Kamaruddin Sellang.This research aims to understand and analyze the role of the Election Supervisory Board (Bawaslu) of Pinrang Regency in overseeing the neutrality of the State Civil Apparatus (ASN) in the 2024 Regional Election. The focus of the research includes three main aspects, namely: (1) prevention (preventive) (2) active supervision (3) law enforcement. The research results show that the Pinrang Regency Bawaslu has carried out its functions through preventive efforts by socializing the principle of ASN neutrality both formally and informally. Active supervision is conducted both directly in the field and digitally through social media monitoring. Law enforcement is carried out through coordination with the National Civil Service Agency (BKN) and the GAKUMDU Center. However, supervision still faces challenges such as budget and human resource limitations. Violations of ASN neutrality often occur in symbolic forms in the digital space and through indirect participation in campaign activities, reflecting a lack of understanding of the principle of "impartiality and non-involvement" as explained by Yamin (2013). Thus, strengthening institutional frameworks, enhancing the capacity of supervisors, and providing continuous education to ASN are crucial for achieving more effective oversight and maintaining the integrity of democracy at the local level.